2022
DOI: 10.1080/07853890.2022.2105393
|View full text |Cite
|
Sign up to set email alerts
|

Person-centred care in individuals with stroke: a qualitative study using in-depth interviews

Abstract: Background Person-centred care (PCC) has considerable effects on the clinical practice of health professionals. The purpose of this study was to describe the perspectives and perceived barriers and enablers of individuals with stroke regarding the PCC model in stroke rehabilitation. Methods A qualitative exploratory study was conducted based on an interpretive framework. Participants were recruited using non-probabilistic purposeful sampling and a snowball-technique str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Increasingly, the ability to provide respectful personalized care, and to build and maintain a therapeutic alliance, is recognized as essential to effective rehabilitation. 21 , 22 Our study added support to emerging findings regarding the importance of person-centered care in neurorehabilitation. There have been increasing calls to better characterize what such care looks like in practice.…”
Section: Discussionsupporting
confidence: 78%
“…Increasingly, the ability to provide respectful personalized care, and to build and maintain a therapeutic alliance, is recognized as essential to effective rehabilitation. 21 , 22 Our study added support to emerging findings regarding the importance of person-centered care in neurorehabilitation. There have been increasing calls to better characterize what such care looks like in practice.…”
Section: Discussionsupporting
confidence: 78%
“… 2 3 It is essential to identify the supportive care needs (SCNs) and provide person-centred care for the rehabilitation and rebuilding of individuals with stroke. 4 Previous studies have confirmed that stroke survivors live with a wide range of physical, 3 psychological, emotional, practical issues, 5 experience disease uncertainty 6 and at a high risk of developing depression, especially in those who have poststroke aphasia. 7 Unmet SCNs of patients who had a stroke will not only decrease their quality of life but also affect their health outcomes negatively.…”
Section: Introductionmentioning
confidence: 96%
“…Most stroke survivors are discharged from the hospital to the community with varying degrees of residual neurological deficits 2 3. It is essential to identify the supportive care needs (SCNs) and provide person-centred care for the rehabilitation and rebuilding of individuals with stroke 4. Previous studies have confirmed that stroke survivors live with a wide range of physical,3 psychological, emotional, practical issues,5 experience disease uncertainty6 and at a high risk of developing depression, especially in those who have poststroke aphasia 7.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of stroke can be profound and lead to a range of activity and participation limitations [9][10][11], such as reduced quality of life, social isolation [12][13][14], and adverse events such as falls [9,15]. Many patients and families describe the support provided poststroke as poor and not patient-centered [16][17][18] and report poor engagement in their care and treatment decisions [7,19]. In addition, the role and importance played by the built environment to support rehabilitation outcomes have been largely ignored, especially when patients return home [20,21].…”
Section: Introductionmentioning
confidence: 99%